Preparation and Evaluation of Physical and, Rheological Properties of Clotrimazole Emulgel - I. Khalil, Yehia; H. Khasraghi, Abeer; J. Mohammed, Entidhar (Iraqi Journal of Pharmaceutical Sciences, 2017)
Recently, emulgel has emerged as one of the most interesting topical preparations in the field of pharmaceutics. In this research clotrimazole was formulated as topically applied emulgel ; different formulas were prepared. The prepared emulgels were evaluated for their physical appearance , rheological behaviour , and in vitro drug release . The influence of the type of gelling agent (carbopol 934 and methyl cellulose), the concentration of both the emulsifying agent (2% and 4% w/w of mixture of span 20 and tween 20) and the oil phase (5% and 7.5% w/w of liquid paraffin) and the type of oil phase (liquid paraffin and cetyl alcohol), on the drug release from the prepared emulgels was investigated. Commercially available topical canestin® cream was used for comparison. All the prepared emulgels showed acceptable physical properties concerning colour, homogeneity, consistency, and pH value. Rheological studies revealed that all emulgels formulations exhibited a shear – thinning behaviour with thixotropy, indicating structural break down of intermolecular interaction between polymeric chains. Clotrimazole emulgels exhibited higher drug release than canestin® cream. The results of in vitro release showed that methyl cellulose – based emulgel gave better release than carbopol 934 – based one. Also it was found that the emulsifying agent concentration had the most pronounced effect on the drug release from the emulgels, followed by the oil phase concentration, which has a retardation effect, and finally the type of the gelling agent. It was suggested that the clotrimazole emulgel formulation prepared with methyl cellulose, with low concentration of oil phase (5%w/w liquid paraffin) and high concentration of emulsifying agent (4%w/w), showed an optimum formula for highest drug release (74.4% after three hours), which followed higuchi diffusion model with a diffusion-controlled mechanism. Key words: Emulgel , carbopol , methyl cellulose , clotrimazole